Application development with Qt Creator build cross-platform applications and GUIs using Qt 5 and C++ - Eng, Lee Zhi (Packt Publishing, 2020)
Application Development with Qt Creator with the latest version of Qt Creator provides an in-depth understanding of Qt's massive library and its functionality. It will enable you to create better modern high-performance apps, exploring cross-platform development and much more.